Layered double hydroxide nanocomposite for drug delivery systems; bio-distribution, toxicity and drug activity enhancement - Kura, Aminu Umar; Hussein, Mohd Zobir; Fakurazi, Sharida; Arulselvan, Palanisamy (Chemistry Central, 2014)
The production of layered double hydroxide(LDH) nanocomposite as an alternative drug delivery system against various ailments is on the increase. Their toxicity potential is usually dose and time dependent with particle sizes, shapes and surface charge playing some role both in the in vitro and in vivo studies. The reticular endothelial system of especially the liver and spleen were shown to sequestrate most of these nanocomposite, especially those with sizes greater than 50 nm. The intracellular drug delivery by these particles is mainly via endocytotic pathways aided by the surface charges in most cases. However, structural modification of these nanocomposite via coating using different types of material may lower the toxicity where present. More importantly, the coating may serve as targeting ligand hence, directing drug distribution and leading to proper drug delivery to specific area of need; it equally decreases the unwanted nanocomposite accumulation in especially the liver and spleen. These nanocomposite have the advantage of wider bio-distribution irrespective of route of administration, excellent targeted delivery potential with ease of synthetic modification including coating.